Orthography in the Cely Letters - Rutkowska, Hanna (Wydawnictwo Naukowe UAM, 2001)
This paper discusses a few important issues concerning the orthography of the Cely letters, including orthographic variation, homography, and problems resulting from the necessity to rely on the edited version of the documents. The level of orthographic standardisation in the corpus is low. It is indicated by the high degree of homography and considerable differences among the authors with regard to orthographic variants used in their letters.
Keywords: ortografia; orthography; pisownia; spelling; korespondencja rodziny Cely; Cely Letters